Penerapan Metode Pembelajaran Student Fasilitator and Explaining untuk meningkatkan Kemampuan Matematis - Muhammad Ihsan (Fakultas Tarbiyah dan Ilmu Keguruan, 2019)
Mathematical communication skills are important in mathematics learning, thus it is expected that the application of Student Facilitator and Explaining learning methods can improve the mathematical communication skills of prospective Mathematics Students at IAIN Palopo. This research is a classroom action research (CAR) with 35 subjects. Data is taken using essay tests and presentation rubrics. Descriptive statistical analysis is the analytical technique used in this study. The results showed that the average score of mathematical communication skills was 69.35 with a percentage of completeness 48.69% in the first cycle and an average of 77.05 with a percentage of completeness of 85.70% in the second cycle and could be categorized as complete classically. The percentage results of the rubric also show a significant increase marked by the frequency of prospective teachers who have been able to convey ideas and concepts in detail and correctly